Direct and indirect effects of crime-related media consumption on public confidence in the police - Choi, Jaeyong (International journal of police science & management, 2020)
This study explores the potential links between crime-related media consumption and confidence in the police based on instrumental and expressive models. Drawing on data from a large sample of South Koreans, direct and indirect effects of crime-related media consumption on perceptions of the police are examined using regression-based multiple mediation analysis. Results showed that although there is no direct effect of media consumption on confidence in the police, crime-related media consumption is significantly and negatively associated with public confidence in the police via perceived incivilities and fear of crime. This study suggests that the police should make a constant effort to develop strategies to enhance communication with the public.